(untitled) (Experimental biology, 2015)
On the ground of measurement analysis of trematodes Pleurogenes intermedius depending on their quantity in one frog, age and size of hosts it was showed that the intraspecific competition is small in the simultaneous presence of 1-5 exemplars of plateworms, then it aggravates in the presence of 6-10 exemplars, and more than 11 exemplars of trematodes in one frog lead to the intraspecific synergism. The role of fibrosis capsule forming around of trematodes in the isolation of parasites each from the other and from the host’s organism was discussed.